2020
DOI: 10.1186/s12967-020-02439-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SARS-CoV-2 RNA-dependent RNA polymerase as a potential therapeutic drug target using a computational approach

Abstract: Background The Severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) outbreak originating in Wuhan, China, has raised global health concerns and the pandemic has now been reported on all inhabited continents. Hitherto, no antiviral drug is available to combat this viral outbreak. Methods Keeping in mind the urgency of the situation, the current study was designed to devise new strategies for drug discovery and/or repositioning against SARS-CoV-2. In the current study, RNA-dependent RNA polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
133
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(146 citation statements)
references
References 64 publications
11
133
0
2
Order By: Relevance
“…In this regard, the computational methods are scientifically sound to design extremely specific inhibitor for viral proteins, as an antiviral drug development/discovery. Recently, structural modeling has predicted a few drugs against SARS-CoV-2 proteins along with many other antiviral drugs [ 2 , 64 , 65 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the computational methods are scientifically sound to design extremely specific inhibitor for viral proteins, as an antiviral drug development/discovery. Recently, structural modeling has predicted a few drugs against SARS-CoV-2 proteins along with many other antiviral drugs [ 2 , 64 , 65 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent molecular docking studies identified nitazoxanide amongst 10 most effective antipolymerase compounds with a docking score -9.76 indicating good binding affinity. Although the score was lower when compared with remdesivir (-14.06), galidesivir (-12.53), ribavirin (-11.88) and sofosbuvir (-11.13) it was comparable to nafamostat (-9.76), interferon (-9.62) and favipiravir (-9.36) ( Aftab et al, 2020 ) proposing great promise. Helicase (nsp13) promotes the separation of double stranded RNA to single stranded RNA mediated through nucleotide triphosphate (NTP) hydrolysis-dependent manner (NTPase) ( Shu et al, 2020 ).…”
Section: Nitazoxanidementioning
confidence: 99%
“…Nitazoxanide not only exhibits the potential to inhibit all these major enzymes, but can also induce autophagy to disrupt protective environment of autophagosomes ( Lam et al, 2012 ; Senkowski et al, 2015 ; Shou et al, 2020 ). Among the enzymes RdRp plays major role in replication of genomic viral RNA, and RdRp of SARS-CoV-2 shares a 96% sequence identity with SARS-CoV ( Aftab et al, 2020 ; Gao et al, 2020 ). Recent molecular docking studies identified nitazoxanide amongst 10 most effective antipolymerase compounds with a docking score -9.76 indicating good binding affinity.…”
Section: Nitazoxanidementioning
confidence: 99%
“…As these five viral proteins are common amongst betacoronaviruses (Woo et al, 2010), it will be useful in studying diverse coronaviruses from diverse hosts, i.e., humans, bat, pangolin, and dog. Presently, we have analyzed CUP of these five proteins in SARS coronavirus, which are considered important targets for vaccine and antiviral development for SARS-CoV-2 (Aftab et al, 2020;Du et al, 2009;Huang et al, 2020;Wu et al, 2020). CUP calculations should be based on highly redundant amino acids rather than amino acids having one or two codons.…”
Section: Introductionmentioning
confidence: 99%